2020
DOI: 10.1021/acsinfecdis.9b00493
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the SAR of the β-Ketoacyl-ACP Synthase Inhibitor GSK3011724A and Optimization around a Genotoxic Metabolite

Abstract: In the course of optimizing a novel indazole sulfonamide series that inhibits β-ketoacyl-ACP synthase (KasA) of Mycobacterium tuberculosis, a mutagenic aniline metabolite was identified. Further lead optimization efforts were therefore dedicated to eliminating this critical liability by removing the embedded aniline moiety or modifying its steric or electronic environment. While the narrow SAR space against the target ultimately rendered this goal unsuccessful, key structural knowledge around the binding site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Lead optimisation efforts of this compound were pursued, but were rendered unsuccessful owing to the detection of a mutagenic aniline metabolite that could not be eliminated due to the limited structure–activity relationship (SAR) space. 79 This exemplifies the copious efforts and resources expended in drug discovery and provides one of an infinite number of reasons as to why promising drug candidates fail to progress through the drug discovery pipeline.…”
Section: Inhibitor and Target Validationmentioning
confidence: 99%
“…Lead optimisation efforts of this compound were pursued, but were rendered unsuccessful owing to the detection of a mutagenic aniline metabolite that could not be eliminated due to the limited structure–activity relationship (SAR) space. 79 This exemplifies the copious efforts and resources expended in drug discovery and provides one of an infinite number of reasons as to why promising drug candidates fail to progress through the drug discovery pipeline.…”
Section: Inhibitor and Target Validationmentioning
confidence: 99%
“…A SAR study was designed to address primary metabolic stability of the compound as evidenced by relatively high clearance rates by microsomes while retaining or improving Mtb potency ( Abrahams et al., 2016 ; Kumar et al., 2018 ; Cunningham et al., 2020 ). The high metabolic turnover of 28 was ascribed to N -demethylation of indazole rendering an inactive compound ( Kumar et al., 2018 ).…”
Section: Antitubercular Agents Inhibiting Mycolic Acid Biosynthesismentioning
confidence: 99%
“…GSK started their own lead optimization program based on the same indazole sulfonamide hit and its demethylated derivative was found to be equipotent to the initial hit ( Cunningham et al., 2020 ). This SAR study similarly found that the n -butyl group (C) was the favored moiety.…”
Section: Antitubercular Agents Inhibiting Mycolic Acid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…GSK3011724A/GSK724 (DG167) 1 , a derivative of indazole sulphonamide, is undergoing early‐stage development of preclinical studies (Figure 2). It is being developed by GlaxoSmithKline and Rutgers, the State University of New Jersey (Cunningham et al., 2020). GSK3011724A is a small molecule active against Mycobacterium tuberculosis and identified from the aforementioned 228 phenotypic screening hits (Rebollo‐Lopez et al., 2015).…”
Section: Tb Drug Development and Their Synthetic Approachmentioning
confidence: 99%